Curry-Odorants and Their Metabolites Transfer into Human Milk and Urine - Debong, Marcel; Homm, Ines; Gigl, Michael; Lang, Roman; Hofmann, Thomas; Büttner, Andrea; Dawid, Corinna; Loos, Helene (Molecular Nutrition & Food Research, 2024)
Scope: The excretion of dietary odorants into urine and milk is evaluated and the impact of possible influencing factors determined. Furthermore, the metabolic relevance of conjugates for the excretion into milk is investigated. Methods and Results: Lactating mothers (n = 20) are given a standardized curry dish and donated one milk and urine sample each before and 1, 2, 3, 4.5, 6, and 8 h after the intervention. The concentrations of nine target odorants in these samples are determined. A significant transition is observed for linalool into milk, as well as for linalool, cuminaldehyde, cinnamaldehyde, and eugenol into urine. Maximum concentrations are reached within 1 h after the intervention in the case of milk and within 2–3 h in the case of urine. In addition, the impact of glucuronidase treatment on odorant concentrations is evaluated in a sample subset of twelve mothers. Linalool, eugenol, and vanillin concentrations increased 3–77-fold in milk samples after treatment with β-glucuronidase. Conclusion: The transfer profiles of odorants into milk and urine differ qualitatively, quantitatively, and in temporal aspects. More substances are transferred into urine and the transfer needs a longer period compared with milk. Phase II metabolites are transferred into urine and milk.
CRIS-Team Scopus Importer:2024-04-19
Keywords: aroma; early flavor learning; glucuronides; odorant metabolism; stir bar sorptive extraction

Dietary Linalool is Transferred into the Milk of Nursing Mothers - Debong, Marcel; N'Diaye, Katharina; Owsienko, Diana; Schoberl, Daniela; Ammar, Tayyaba; Lang, Roman; Büttner, Andrea; Hofmann, Thomas; Loos, Helene (Molecular Nutrition & Food Research, 2021)
Scope: Breast milk is repeatedly postulated to shape the first aroma and taste impressions of infants and thus impact their flavor learning. The objective of this study is to assess the transition of aroma compounds from a customary curry dish into milk. Methods and Results: The article prepares a standardized curry dish and administers the dish to nursing mothers (n = 18) in an intervention study. The participants donate one milk sample before and three samples after the intervention. Due to their olfactory or quantitative relevance in the curry dish, 1,8-cineole, linalool, cuminaldehyde, cinnamaldehyde, 4-hydroxy-2,5-dimethyl-3(2H)-furanone, sotolone, eugenol, vanillin, and γ-nonalactone are defined as target compounds, and their transition into milk is quantified by gas chromatography-mass spectrometry. A significant transition into the milk is observed for linalool, and its olfactory relevance in this respect is supported by calculated odor activity values. In contrast, no relevant levels are detected for the other eight target compounds. Conclusion: Ingestion of a customary curry dish can lead to an alteration of the milk aroma, which might be perceived by the infant during breastfeeding. The current study also demonstrates that the extent of aroma transfer differs between both substances and individuals.
Created from Fastlane, Scopus look-up
Keywords: aroma transition; breast milk; flavor learning; linalool; maternal diet

Dietary Piperine is Transferred into the Milk of Nursing Mothers - N´Diaye, Katharina; Debong, Marcel; Behr, Jürgen; Dirndorfer, Sebastian; Duggan, Tara; Beusch, Anja; Schlagbauer, Verena; Dawid, Corinna; Loos, Helene; Büttner, Andrea; Lang, Roman; Hofmann, Thomas (Molecular Nutrition & Food Research, 2021)
Introduction: The diet of breastfeeding mothers could bring nurslings into contact with flavor compounds putatively contributing to early sensory programming of the infant. The study investigates whether tastants from a customary curry dish consumed by mothers are detectable in their milk afterwards and can be perceived by the infant. Methods and Results: Sensory evaluation identifies pungency as the dominating taste impression of the curry dish. Its ingredients of chili, pepper, and ginger suggest the flavor compounds capsaicin, piperine, and 6-gingerol as analytical targets. Breastfeeding mothers are recruited for an intervention trial involving the consumption of the curry dish and subsequent collection of milk samples for flavor compound analysis. Targeted and untargeted mass spectrometric (MS)- investigations identify exclusively piperine as an intervention-derived compound in human milk. However, concentrations are below the human taste threshold. Conclusion: Piperine from pepper-containing foods transfers into the mother's milk within 1 h and is delivered to the nursling. Concentrations of 50 and 200 nM of piperine are 70–350 times below the human taste threshold, but TRPV1 (Transient Receptor Potential Vanilloid-1 ion channel) desensitization through frequent exposure to sub-taste-threshold concentrations could contribute to an increased tolerance at a later age.
CRIS-Team Scopus Importer:2021-10-29
Keywords: human milk; metabonomics; piperine; sensory programming

Diet-Induced Flavor Changes in Human Milk: Update and Perspectives - Debong, Marcel; Loos, Helene (Journal of Agricultural and Food Chemistry, 2020)
Dietary aroma transfer into human milk has been studied in many scenarios, including direct transmission and biotransformation. This perspective highlights recent research that focuses on the latter, with examples given in relation to 1,8-cineole and garlic-derived odorants. Three future directions are discussed, comprising (a) achieving a more comprehensive understanding of the chemical and physiological basis of aroma transfer into milk via pharmacological methods, advanced analytical techniques, and ecologically valid study designs, (b) assessing the bioactivity of odorants and their metabolites present in milk that are ingested by the infant, and (c) translating the insights gained on aroma transmission in relation to taste attributes and bioactive components of the maternal diet.
CRIS-Team Scopus Importer:2020-02-14
Keywords: 1; 8-cineole; aroma transfer; breastfeeding; garlic; human milk; odorant metabolism

Geruchsstoffmetabolismus im Menschen - Kornbausch, Nicole; Debong, Marcel; Büttner, Andrea; Heydel, Jean-Marie; Loos, Helene (Angewandte Chemie, 2022)
Geruchsstoffe sind verhältnismäßig kleine Moleküle, welche vom menschlichen Körper leicht aufgenommen werden können. Trotz ihrer großen Relevanz im Alltag ist vergleichsweise wenig über ihren Metabolismus, ihre Verteilungswege und ihre Bioaktivität im menschlichen Körper bekannt. Mit diesem Aufsatz möchten wir zu interdisziplinärer Forschung an den Schnittstellen zwischen Ernährungswissenschaften, Medizin, Biochemie, Chemie und Wahrnehmungswissenschaften beitragen, um das Wissen über die Mechanismen und Funktion der Biotransformation von Geruchsstoffen zu erweitern. Innerhalb des Artikels wird zunächst ein allgemeiner Überblick über die Aufnahme von Geruchsstoffen und die bei der Verstoffwechselung beteiligten Enzyme gegeben. Anschließend wird speziell auf die Biotransformation im Mund- und Nasenraum sowie in der Lunge und im Gastrointestinaltrakt eingegangen, und die verschiedenen Ausscheidungswege werden aufgezeigt. Schließlich wird ein Ausblick auf die zukünftige Forschung gegeben und diskutiert.<br

Linalool, 1,8-Cineole, and Eugenol Transfer from a Curry Dish into Human Urine - Debong, Marcel; N'Diaye, Katharina; Schöberl, Daniela; Yin, Yue; Lang, Roman; Büttner, Andrea; Hofmann, Thomas; Loos, Helene (Molecular Nutrition & Food Research, 2023)
Scope: For most substances, there are several routes of excretion from the human body. This study focuses on urinary excretion of dietary odorants and compares the results with previously obtained results on excretion into milk. Methods and results: Lactating mothers (n = 18) are given a standardized curry dish and donate urine samples before and after the intervention. The odorants 1,8-cineole, linalool, cuminaldehyde, cinnamaldehyde, 4-hydroxy-2,5-dimethyl-3(2H)-furanone, sotolone, eugenol, vanillin, and γ-nonalactone are quantitatively analyzed. A significant transition of up to 6 µg g−1 creatinine into urine is observed for linalool, 1,8-cineole, and eugenol. Maximum concentrations are reached 1.5 h after the intervention for 1,8-cineole and eugenol as well as 2.5 h after the intervention for linalool. Comparison with previous results reveals that the excretion pattern of odorants into urine is divergent from the one into milk. In a second intervention study (n = 6), excretion of phase II metabolites into urine is studied using β-glucuronidase treatment. Linalool and eugenol concentrations are 23 and 77 times higher after treatment than before treatment with β-glucuronidase, respectively. Conclusion: The study demonstrates transition of linalool, 1,8-cineole, and eugenol from the diet into urine and excretion of glucuronides in the case of linalool, eugenol, and vanillin.
CRIS-Team Scopus Importer:2023-12-08
Keywords: aroma transition; gas chromatography-mass spectrometry/olfactometry; maternal diet; milk; phase II-metabolism

Odorant Metabolism in Humans - Kornbausch, Nicole; Debong, Marcel; Büttner, Andrea; Heydel, Jean-Marie; Loos, Helene (Angewandte Chemie International Edition, 2022)
Odorants are relatively small molecules which are easily taken up and distributed in the human body. Despite their relevance in everyday life, however, only a limited amount of evidence about their metabolism, pathways, and bioactivities in the human body exists. With this Review, we aim to encourage future interdisciplinary research on the function and mechanisms of the biotransformation of odorants, involving different disciplines such as nutrition, medicine, biochemistry, chemistry, and sensory sciences. Starting with a general overview of the different ways of odorant uptake and enzymes involved in the metabolism of odorants, a more precise description of biotransformation processes and their function in the oral cavity, the nose, the lower respiratory tract (LRT), and the gastrointestinal tract (GIT) is given together with an overview of the different routes of odorant excretion. Finally, perspectives for future research are discussed.
CRIS-Team WoS Importer:2022-08-26

Tracing odour- and taste-active compounds in human milk - Debong, Marcel; Lang, Roman; N'Diaye, Katharina; Büttner, Andrea; Hofmann, Thomas; Loos, Helene (Proceedings of the 16th Weurman Flavour Research Symposium, 2021)
Scope The alteration of the flavour of human milk by the maternal diet and thereby the possibility of sensory programming of the infant has been reported in several studies. The objective of this study was to exemplarily illustrate and compare the simultaneous transition of odour-and taste-active compounds from a customary curry dish into milk. Methods and Results A standardised curry dish was prepared and its flavour-active compounds were characterised. This dish was used in an intervention study with lactating mothers who donated four milk samples, one before and three after the intervention. These samples were used to quantify the transition of flavour-active compounds from the curry dish into milk via GC-MS and LC-MS. The concentration courses of linalool, 1,8-cineole and piperine are illustrated here for the milk samples of three exemplary test persons. These courses demonstrate a transition after the intervention as well as interindividual variations regarding transition time and amounts. Conclusion Flavour-active substances can migrate from the maternal diet into human milk. The transferred compounds do not necessarily reach concentrations perceivable by adults. Though, even at below threshold concentrations, the transferred compounds can interact with the nurslings’ receptor sand induce physiological changes in the chemosensory system.<br
Keywords: curry; metabonomics; piperine; linalool; 1; 8-cineol